Новые виды пухоедов рода Philopterus (Mallophaga, Philopteridae) от вьюрковых и ткачиковых птиц фауны СССР - Федоренко, И.А. (Вестник зоологии, 1984)
Philopterus petrinus sp. n.- differs from Ph. fringillae (Scopoli) in head structure, clypeal plates shape and female genital clasp chetotaxy. Host: Rock sparrow. Type-localiy: Turkmen SSR. Ph. smogorzewskyi sp. n.- differs from Ph. linariae (Piaget) in paler colouration, metathorax and tergal abdominal plates chetoraxy. Host: Gold- fronted serin. Type-locality: Azerbaijan SSR. Ph. rhodospizae sp. n.- similar to Ph. smogorzewskyi, differs from it in head shape and structure, female clypeal and genital plates, and in chetotaxy of abdominal tergopleural plates and genital clasp margin in female. Host: Desert finch. Type-locality: Turkmen SSR.